Break-Even Point Analysis Of A Simple Tofu Factory Business In Cahaya Negeri, Seluma Regency - Nigita, Wayan; Wagini, Wagini; Febliansa , M. Rahman (Journal of Management, Economic, and Accounting, 2025)
The purpose of this study is, , to determine the Break Even Point Analysis as a tool in profit planning at the Simple Tofu Factory Business in Cahaya Negeri Seluma Regency in the period June to August 2024. The method used in this research is quantitative descriptive method.The research results indicate that, based on BEP calculations, the small-scale tofu factory business reaches its monthly break-even point with a sales volume of 4,429 tofu units or revenue of Rp199,330,735. For a three-month period, the break-even point is achieved at 13,288 units or Rp597,992,211. Over three months, actual sales reached 18,000 units, generating a net profit of Rp49,004,000 with a profit margin of 6.05%. Furthermore, with a 20% profit plan, this business shows potential to increase net profit by up to 20%, with a target monthly sales of 6,073 units or revenue of Rp273,266,933. Recommendations for the business include setting sales targets based on the BEP and expanding distribution to increase sales volume and market reach.